2019
DOI: 10.1007/s12639-019-01088-5
|View full text |Cite
|
Sign up to set email alerts
|

Designing and standardizing Toxocara serologic diagnostic kit and determining anti-Toxocara antibodies frequency in patients referred to health care centers in Urmia (northwest of Iran)

Abstract: Toxocariasis is a helminthic zoonosis caused by larval stages of the roundworm of dog, Toxocara canis, and less frequently by T. cati, the roundworm of cats. Eosinophilia in peripheral blood may be indicative of a disease; however, it does not necessarily represent toxocariasis. Therefore, it is necessary to investigate the relationship between eosinophilia and toxocariasis in a region. The aims of this study were the diagnosis of hyperosinophilia patients using traditional ELISA kit and also by a handmade ELI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Similar to previous studies, we have not found an association between Toxocara seropositivity and the age ( Dattoli et al, 2011 ; Khozime et al, 2018 ) or gender ( Ashtari et al, 2019 ; Khozime et al, 2018 ) of the allergic patients. However, two studies from South Korea had reported higher Toxocara seropositivity among male patients ( Song et al, 2020 ; Yoon et al, 2018 ), particularly those with a history of consuming the raw meat/livers of animals and heavy alcohol consumption ( Song et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to previous studies, we have not found an association between Toxocara seropositivity and the age ( Dattoli et al, 2011 ; Khozime et al, 2018 ) or gender ( Ashtari et al, 2019 ; Khozime et al, 2018 ) of the allergic patients. However, two studies from South Korea had reported higher Toxocara seropositivity among male patients ( Song et al, 2020 ; Yoon et al, 2018 ), particularly those with a history of consuming the raw meat/livers of animals and heavy alcohol consumption ( Song et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of Toxocara eggs has been strongly correlated with the moisture content of soil ( r = 0.799; p = 0.027) ( Paller et al, 2014 ). A study from Iran reported a strong correlation between the prevalence of T. canis excretory-secretory (TCES)-specific IgG antibodies and contact with soil ( p < 0.001), dogs ( p < 0.001), and residing in a village ( p = 0.006) ( Ashtari et al, 2019 ). Another study reported higher prevalence rates of T. cati (28.5%) and T. canis (13.8%) in humans in the northern regions of the Iran due to optimum climate conditions and close contact between humans and host animals ( Eslahi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%